2014
DOI: 10.4269/ajtmh.13-0616
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Interleukin-10 Gene Promoter Polymorphisms and Risk of Endemic Burkitt Lymphoma

Abstract: Abstract. Overexpression of interleukin-6 (IL-6) and IL-10 in endemic Burkitt lymphoma (eBL) may facilitate tumorigenesis by providing a permissive cytokine milieu. Promoter polymorphisms influence interindividual differences in cytokine production. We hypothesized that children genetically predisposed for elevated cytokine levels may be more susceptible to eBL. Using case-control samples from western Kenya consisting of 117 eBL cases and 88 ethnically matched healthy controls, we tested for the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The levels of IL-6, an inflammatory cytokine, in BL participants in this study were higher, though not statistically significant, but similar in trend to Aka et al [ 14 ]. The relatively high levels of IL-6 cytokines in BL than in non-BL participants was also comparable to earlier reports of increased levels of IL-6 and other inflammatory cytokines in lymphomas by Mellgren et al [ 15 ], but different from Oduor et al [ 16 ], who reported no association between IL-6 expression and BL. A study by Chopra et al [ 17 ] demonstrated increased IL-6 levels in BL cases compared to healthy controls.…”
Section: Main Textsupporting
confidence: 89%
“…The levels of IL-6, an inflammatory cytokine, in BL participants in this study were higher, though not statistically significant, but similar in trend to Aka et al [ 14 ]. The relatively high levels of IL-6 cytokines in BL than in non-BL participants was also comparable to earlier reports of increased levels of IL-6 and other inflammatory cytokines in lymphomas by Mellgren et al [ 15 ], but different from Oduor et al [ 16 ], who reported no association between IL-6 expression and BL. A study by Chopra et al [ 17 ] demonstrated increased IL-6 levels in BL cases compared to healthy controls.…”
Section: Main Textsupporting
confidence: 89%
“…A number of meta-analysis of the IL-6 gene polymorphisms with cancer risk were conducted based on small sample sizes [ 123 130 ]. Some GWA studies have also reported that some polymorphisms of the IL-6 gene are insignificantly associated with blood cancer [ 13 25 ] and significantly associated with breast cancer [ 26 36 ] whereas some other studies [ 37 – 40 ] reported no association with breast cancer. Similarly, for cervical and colon cancer development, some studies reported a significant association [ 41 46 and 49 56 respectively] whereas other studies reported no significant association [ 44 , 47 , 48 , 57 61 respectively].…”
Section: Introductionmentioning
confidence: 99%
“…Complete linkage disequilibrium exists between the alleles at positions ‐819 and ‐592 . In addition, other diseases including gastric cancer, colorectal cancer, inflammatory bowel disease, chronic hepatitis and haematologic disease are significantly associated with IL10 polymorphisms .…”
Section: Introductionmentioning
confidence: 99%